The resistance response of sunflower genotypes to black stem disease under controlled conditions - DARVISHZADEH, Reza; PIRZAD, Alireza; DANESH, Younes Rezaee; SARRAFI, Ahmad (Phytopathologia Mediterranea, 2010)
Phoma black stem, caused by Phoma macdonaldii, is one of the most important diseases of sunflower in the world. The sources of resistance to Phoma black stem were investigated. A total of 184 genotypes, including some recombinant inbred lines (RILs), several M6 mutant lines obtained by gamma irradiation of seed of the genotype AS 613, and other genotypes from different countries, were evaluated against an aggressive French isolate (MP6) in controlled conditions. The study was carried out in a randomized complete block design with three replicates. Each replicate consisted of 10–12 seedlings. Twenty μL of spore suspension (106 pycnidiospores mL-1) were deposited on the intersection of the cotyledon petiole and the hypocotyl of sunflower plantlets at the two-leaf stage. The percentage of the area exhibiting disease symptoms was scored on the two cotyledon petioles of each of the plantlets three, five and seven days after inoculation. The disease progress rate (rd), as the slope of the regression line for disease severity against time, was also calculated. Analysis of variance detected significant differences among sunflower genotypes for disease severity 7 days after inoculation, as well as for the disease progress rate. A strong correlation (r=0.96, P<0.01) was found between disease severity 7 days after inoculation and the disease progress rate. The inbred lines F1250/03 (origin: Hungary), M5-54-1, M6-862-1 (mutant lines), SDR 18 (origin: USA) and two wild Helianthus accessions, 1012 Nebraska and 211 Illinois, (wild type) were highly resistant to Phoma black stem. These findings will assist breeders in choosing parent plants for breeding durable resistance to Phoma black stem.